Associations between affective distress, alcohol use, and cognitive flexibility: moderating effects of COMT Val158Met genotype - Cody A. Mashburn; Emily M. Clarke; Sharon M. Pearcey; Emily M. Pogue; Bilal Saleem; Erica D. Holliday (Frontiers in Public Health, 2026)
Background Alcohol use is common during emerging adulthood and has been associated with impairments in executive functioning, including cognitive flexibility. Individual differences in affective distress, early life adversity, and genetic variation in dopaminergic signaling pathways may contribute to variability in cognitive flexibility among young adults. The present study examined the relationships among proximal affective distress, distal early life stress, alcohol use, and the functional COMT Val158Met polymorphism. Methods Seventy-two college-aged adults completed measures of adverse childhood experiences (ACEs), affective distress, alcohol use, and cognitive flexibility. Cognitive flexibility was assessed using both behavioral measures from a Number-Letter task and self-reported cognitive flexibility using the Cognitive Flexibility Inventory (CFI). An exploratory factor analysis was conducted on measures of depression, anxiety, stress, affect, and state–trait anxiety to derive a latent affective distress factor. General linear models examined the effects of affective distress, drinking status, and COMT Val158Met genotype, on cognitive flexibility outcomes. Results Higher affective distress was associated with lower scores on the CFI Control subscale, indicating reduced perceived behavioral control. This relationship was significantly stronger among individuals reporting alcohol use. Affective distress also interacted with drinking status to predict behavioral cognitive flexibility, such that greater distress was associated with poorer task-switching performance only with prior alcohol use. This interaction was further moderated by COMT genotype. Specifically, Val/Val individuals showed greater reductions in cognitive flexibility conditions of elevated affective distress and alcohol use, whereas Met-carriers showed relatively stable performance across conditions. ACEs were positively associated with affective distress but did not predict cognitive flexibility outcomes. Conclusion Proximal affective distress, but not early life adversity, emerged as a key correlate of both perceived and behavioral cognitive flexibility in emerging adults, particularly among individuals reporting alcohol use. COMT genotype moderated these relationships, suggesting that dopaminergic variation may influence sensitivity to current affective and alcohol-related cognitive demands with limited impacts from early life stress. These findings highlight the importance of considering affective, behavioral, and biological factors jointly when examining cognitive flexibility and alcohol-related risk during emerging adulthood.